Predictors of child abuse in maritally violent families - O'Keefe, M. (Journal of interpersonal violence, 1995)
The focus of the present study was twofold: (a) to examine the differences between children from maritally violent homes who witnessed marital violence and those who were both witnesses as well as victims of abuse; and (b) to determine the best predictors of child abuse among maritally violent families. Participants included 184 children, ages 7 to 13, and their mothers who were residing at battered women shelters. Compared to children who witnessed interparental violence, children who were both witnesses as well as victims of physical abuse scored significantly higher on externalizing behavior problems. A stepwise logistical regression analysis identified numerous predictors of child abuse among maritally violent families. These included a greater frequency and severity of marital violence, less marital satisfaction, and a poorer quality of father-child relationship as perceived by the children. In addition, children from families where child abuse occurred were more likely to exhibit aggressive behavior problems than children who only witnessed marital violence